UJI BERBAGAI JENIS MATRICONDITIONING TERHADAP VIABILITAS DAN VIGOR BENIH PADI GOGO LOKAL VARIETAS BUYUNG (Oryza sativa L.): TEST OF VARIOUS TYPES OF MATRICONDITIONING ON THE VIABILITY AND VIGOR OF LOCAL GOGO RICE SEEDS OF THE BUYUNG VARIETY (Oryza sativa L.) - Suparto, Hairu; Gazali, Akhmad; Widyawati, Wahyu; Rahmatillah, Fairuz (AgriPeat, 2024)
This research is aimed to know the effect of some kinds of matriconditioning against viability and vigor of Buyung variety rice seed. Arranged by randomised block design with single factor consisting of 8 treatments and four repeats. The Research result is obtained that treatment of some kinds of matriconditioning have very real effected against observation variable of viability and vigor of Buyung variety as local upland rice seed (Oryza sativa.L). The best kind of matriconditining is combining of husk charcoal, sawdust and rice straw. It can increase germination, growth synchronously, growth speed and maximum growth potential